Public Management as Corporate Social Responsibility The Economic Bottom Line of Government - Di Bitetto, Massimiliano.; Di Bitetto, Massimiliano.; Chymis, Athanasios.; Chymis, Athanasios.; D'Anselmi, Paolo.; D'Anselmi, Paolo. (CSR, Sustainability, Ethics & Governance, 2015)
This collection of case studies in public management bridges the gap between mainstream CSR - confined to the for-profit corporations - and the vast bodies of workers and organizations that make up government and its public administration. The variety and discretion of managerial endeavours in public management calls for accountability and responsibility of government beyond current legal instruments: The book argues that CSR must be brought to bear with government. In government in fact, knowledge management is not a linear process, but the result of working with passion of the parts, implying discretionary behaviour and creativity which in turn imply choice and responsibility. Cases ranging from the USA to Central America, New Zealand and Europe all confirm the complex nature of public management, entailing partnership synergy for disaster recovery, the intertwined link between management and new technology and mindfulness at individual level. The cases are set in a framework by theoretical essays on bureaucratic behaviour and unknown stakeholders. Public-sector management has long drawn upon principles, tools, and techniques developed in the private sector, aiming to infuse bureaucracies with touches of efficiency and productivity. But good governance is also central to good management. This fascinating, wide-ranging volume shows how ideas from the Corporate Social Responsibility movement apply to the governance and administration of public agencies. A series of detailed and informative case studies, written by researchers and practitioners with deep knowledge of their industries and agencies, explores the challenges of managing public and government agencies in a socially responsible manner. The book offers a nuanced and balanced portrait that calls for greater public involvement and oversight in keeping public organizations on track. Highly recommended! Peter G. Klein University of Missouri Norwegian School of Economics and Mises Institute Here are six compelling case studies that reveal the relevance, even the imperative, of Corporate Social Responsibility (CSR) in the public sector. In doing so, the authors simultaneously expand the role of CSR and provide us with a refreshed concept of government and public management. The authors then lay the theoretical groundwork for their observations in ways that enrich our understanding of both CSR and the evolving roles of government in our lives. This is “must reading” for corporate officers and for public managers. Thomas R. Sexton Stony Brook University,  NY College of Business and School of Professional Development.